Echocardiography-Guided Management of Preterms With Patent Ductus Arteriosus Influences the Outcome: A Cohort Study - Terrin, Gianluca; Di Chiara, Maria; Boscarino, Giovanni; Versacci, Paolo; Di Donato, Violante; Giancotti, Antonella; Pacelli, Elisabetta; Faccioli, Francesca; Onestà, Elisa; Corso, Chiara; Ticchiarelli, Alessandra; De Curtis, Mario (Frontiers in Pediatrics, 2020)
Introduction: Echocardiography (ECHO) with color flow doppler is considered the gold standard to identify a hemodynamic patent ductus arteriosus (hs-PDA). However, the optimal diagnostic and therapeutic management for newborns with hs-PDA is still controversial. We aimed to investigate two clinical strategies: 1) targeted treatment based on ECHO criteria; 2) treatment based on ECHO criteria in addition to clinical signs and symptoms. Materials and Methods: A Cohort study including all neonates consecutively admitted in the Neonatal Intensive Care Unit (NICU) of University La Sapienza in Rome, with gestational age (GA) <32 weeks or body birth weight (BW) <1500 g, with diagnosis of hs-PDA confirmed by ECHO evaluation performed within 72 hours of life. We classified the babies in two Cohorts: A) pharmacological treatment immediately after ECHO screening; B) pharmacological therapy for PDA was administered when the relevance of a hs-PDA, was associated with clinical signs of hemodynamic instability. Results: We considered as primary outcome newborns survived without any morbidities (A 48.1% vs B 22.2%, p = 0.022). In particular, we found that the rate of intraventricular hemorrhage (IVH) stage ≥ 2 was increased in Cohort B (A 3.7% vs. B 24.4%, p = 0.020). Multivariate analysis showed that assignment to Cohort A independently influences the primary outcome. Conclusions: To adopt hs-PDA management option based on ECHO directed therapy regardless of symptoms may reduce morbidity and improve survival of very low birth weight (VLBW) infants.